A statistical and spatial analysis of water poverty using a modified Water Poverty Index. Issue 2 (4th March 2021) - Prince, Breeanna C.; Juran, Luke; Sridhar, Venkataramana; Bukvic, Anamaria; MacDonald, Morgan C.
ABSTRACT: This study advances methods of measuring access to water by providing a framework that can be operationalized by practitioners to inform decision and policy making. A modified WPI was developed and deployed in India, with results indicating significant differences between WPI and many indicator scores both between and within administrative territories. Spatial analyses identified significant clustering of WPI and indicator scores, indicating that scores are not randomly distributed. Three weight schemes were applied, two of which were informed by local stakeholders. The weight schemes highlighted the subjectivity of weighting and importance of including local populations in water development and management.